2017
DOI: 10.1007/s13187-017-1225-4
|View full text |Cite
|
Sign up to set email alerts
|

Advance Care Planning Communication: Oncology Patients and Providers Voice their Perspectives

Abstract: Advance care planning helps to ensure that patients' end-of-life preferences are understood and discussed with providers. It is an important component of patient-centered care, particularly when patients are facing life-limiting illness. It also has ethical implications for providers, yet evidence suggests that these conversations are not always occurring, particularly in underserved populations. The aim of this study was to understand the challenges and personal beliefs regarding ACP through interviews with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(32 citation statements)
references
References 12 publications
1
31
0
Order By: Relevance
“…Of the 52 patients with recurrent disease who were undergoing active treatment for their recurrence, 38 patients (73.1%) knew about ACP. This is similar to Bires’ survey of 20 patients which found that 14 (70%) were aware of ACP (Bires et al, ). Pfirstinger noted that awareness of a form of ACP (in this case, the possibility of assigning a healthcare proxy) was low among new patients admitted to a haematology/oncology outpatient clinic (Pfirstinger et al, ).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…Of the 52 patients with recurrent disease who were undergoing active treatment for their recurrence, 38 patients (73.1%) knew about ACP. This is similar to Bires’ survey of 20 patients which found that 14 (70%) were aware of ACP (Bires et al, ). Pfirstinger noted that awareness of a form of ACP (in this case, the possibility of assigning a healthcare proxy) was low among new patients admitted to a haematology/oncology outpatient clinic (Pfirstinger et al, ).…”
Section: Resultssupporting
confidence: 88%
“…Awareness of ACP was examined by four of the studies in this review (Bires et al, ; Brown et al, ; Carrion et al, ; Pfirstinger et al, ). Brown et al surveyed 110 cancer patients regarding their knowledge of a form of ACP and found that nearly a quarter (24.8%) of all patients had no knowledge of ACP (Brown et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations